Health Behaviors of Centenarians are Worth Attention - Xianglong Xu (Archives of Nursing Practice and Care - Peertechz Publications, 2015)
In contemporary society, it's important to prevent and minimize the impact of non-communicable disease [1]. Health behaviors, such as physical inactivity, smoking, obesity, poor diets, and alcohol misuse are among the most common causes of disease and premature deaths in the world [2,3]. With the  development of the economy and the level of medical and health care, the proportion of the elderly  population is becoming big, and the number of centenarians is increasing both in China and many other developing countries.